PERLINDUNGAN TERHADAP KONSUMEN DALAM PERJANJIAN TRANSAKSI JUAL BELI ONLINE - Axdiaz Resky Setiawan (CV. Multi Kreasi Media, 2023)
Legal protection for consumers in buying and selling transactions online is very important for the development of the people's economy. Online buying and selling transactions are basically the same as conventional buying and selling, the difference is the media used. When business actors and consumers enter into an agreement, both parties are bound and have obligations and rights that must be fulfilled. The problem in this writing is how business actors are accountable to consumers in online buying and selling transactions and how legal protection is for consumers in online buying and selling transaction agreements. By using normative legal research methods. The results of the study are, First, the responsibility for business actors in buying and selling online is to provide compensation or compensation for problematic products. Second, legal protection for online shopping consumers can be provided in terms of legal certainty contained in laws and regulations governing online shopping, namely Law Number 19 of 2016 amendment to Law Number 11 of 2008 Concerning Information and Electronic Transactions and Law -law no. 8 of 1999 concerning Consumer Protection.